Hubungan Dukungan Sosial dengan Stres Akademik Mahasiswa Universitas Muhammadiyah Sidoarjo - Ansyah, Eko Hardi; Susanti, Putri Nanda (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2023)
Individuals who start in universities will change their status from school students to college students in themselves. The demands and obstacles of college students during their studies must be resolved, if they are not resolved, they can trigger the emergence of stressors which are affect the appearance of psychological disorders such as symptoms of academic stress. One of the factor that influence academic stress is social support. The purpose of this research was to determine the relationship between social support and academic stress in college students of Muhammadiyah Sidoarjo University. This research was a correlational quantitative research with simple random sampling as techniques for sample selection. Populations of this research was 2145 college students Psychology and Education faculty of Muhammadiyah Sidoarjo University with 301 respondents as sample. The data collection technique used a psychological scale with a Likert scale model consisting of a social support scale and an academic stress scale arranged based on scale aspects. The data analysis technique used was a product-moment correlation technique assisted by spss 21.0 for windows. The results of the data analysis obtained rxy=-0,264** with a sig value 0,000, then the hypothesis proposed by the researcher was accepted. It means there is a negative relationship between social support and academic stress on Muhammadiyah Sidoarjo University college students. Keywords: Social Suport; Acedemic Stress; College Students